REKONSTRUKSI PEMIKIRAN YURIDIS INTEGRAL DALAM PEMBAHARUAN SISTEM HUKUM JAMINAN FIDUSIA BERPILAR PANCASILA - Sri Mulyani (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2010)
Review the renewal of national legal systems there are big problems in the national legal system that is ius constitutum (problem of